2017
DOI: 10.24914/jeb.v20i1.611
|View full text |Cite
|
Sign up to set email alerts
|

Paradoks Ganda Kos Produksi Petani Tembakau (Studi Fenomenologi pada Petani Tembakau di Kabupaten Jember)

Abstract: ABSTRAKFenomena paradoks ganda kos produksi akibat pasar tembakau merupakan kajian penelitian ini. Kajian ini merujuk akibat transaksi harga yang bersifat oligopsoni dan petani tidak memiliki akses langsung ke pabrik. Paradoks seperti ini membuat kondisi antara petani dan pabrik menentukan beban produksi. Beban produksi yang terjadi akibat proses jual-beli diperantarai oleh tengkulak, sehingga fluktuasi harga tembakau merugikan petani. Penelitian ini mengunakan studi fenomena. Hasil penelitian mewujudkan harmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
6
Order By: Relevance
“…The research was conducted in two ways, namely in-depth interviews to reveal the real condition of object and direct observation (Prasetyo, 2017). These two methods are to reveal the labuhan larung sesaji cosmology ritual of fishermen for the homogeneity strategic cost concept.…”
Section: Methodsmentioning
confidence: 99%
“…The research was conducted in two ways, namely in-depth interviews to reveal the real condition of object and direct observation (Prasetyo, 2017). These two methods are to reveal the labuhan larung sesaji cosmology ritual of fishermen for the homogeneity strategic cost concept.…”
Section: Methodsmentioning
confidence: 99%
“…Middlemen as factory partners determine the price, and this is an oligopsonistic market, making farmers unable to enter the factory. The results of research conducted by Rokhmah [9] and Rachmad [10] found that tobacco pricing is a speculative transaction, meaning that profit-seeking motive of the middlemen is more dominant because the transaction does not end with the delivery of goods, so that prices are fixed regardless of the quality, so farmers have no bargaining power [4].…”
Section: Advances In Engineering Research Volume 172mentioning
confidence: 99%
“…The mechanism of the oligopsonistic tobacco trading system enables a number of warehouses owned by a small number of manufacturers to play a role in the "capacity" of the warehouse so that farmers are willing to sell their crops at the cheapest prices, positioning farmers as the disadvantaged party. A situation like this makes a "purchase schedule" to be mocked to reduce the price of farmers' tobacco [4]. The internal and external problems depress tobacco prices.…”
Section: Challenges Of Government Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tobacco is one of the plantation crops produced in the territory of Indonesia besides tea, oil palm, and sugar cane. Moreover, the number of workers in the tobacco sector in Indonesia, particularly tobacco farmers, is currently around 689,360 people, with a total area of 221 thousand hectares planted with tobacco spreading across 15 provinces [4].…”
Section: Introductionmentioning
confidence: 99%